Testing the diathesis‐stress model: 5‐HTTLPR, childhood emotional maltreatment, and vulnerability to social anxiety disorder12. Issue 3 (8th March 2013) - Reinelt, Eva; Stopsack, Malte; Aldinger, Maren; John, Ulrich; Grabe, Hans Jörgen; Barnow, Sven
Abstract Regarding the development of social anxiety disorder (SAD), a diathesis‐stress paradigm including biological vulnerabilities and environmental stressors can be assumed. However, studies dealing with the etiology of SAD did not integrate both aspects so far. We examined a particular diathesis‐stress model for SAD in which we included a functional polymorphism of the serotonin transporter (5‐HTTLPR) as a genetic vulnerability factor and childhood emotional maltreatment (CEM) as an environmental stressor. Current analyses were based on individuals who participated in the Study of Health in Pomerania. Psychiatric disorders were assessed with diagnostic interviews according to DSM‐IV criteria. The triallelic genotype of 5‐HTTLPR was determined. Statistical analyses were performed in 78 individuals with SAD and 1, 035 without an axis I disorder. Logistic regression analysis revealed that the experience of CEM (odds ratio [OR] 4.56; 95% confidence interval [CI] 2.65–7.84), the l/l genotype of 5‐HTTLPR (OR 2.13; 95% CI 1.31–3.48), female gender (OR 3.03; 95% CI 1.80–5.08) and younger age (OR 1.04; 95% CI 1.02–1.06) increased the odds for SAD. The data suggest that CEM, the l/l genotype of 5‐HTTLPR, female gender and younger age are risk factors for SAD. This is in favor of the tested diathesis‐stress model. © 2013 Wiley Periodicals, Inc.